Improved soil fertility in Benin - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
Farmer groups in Benin have found that the leguminous ground creeper, mucuna, serves two purposes: it suppresses pernicious weeds and builds up soil fertility. In the late 1980s, the Institut National des Recherches Agricoles du Benin (INRAB) began...